"Allah n’est pas obligé" d’A. Kourouma : un palimpseste ivoirien // Kourouma’s "Allah is not obliged", a palimpsest from the Ivory coast - Zuzana Malinovská (Svět Literatury, 2015)
The present study shows that the novel Allah Is Not Obliged (2000) by Ahmadou Kourouma from the Ivory Coast, is an up-dated “Africanized“ transposition of Journey to the End of the Night (1932), L-F. Céline’s key 20th century French novel despite the lapse of time and different contexts, in which both works originated. After a brief introduction of contexts and Kourouma’s problem of ambivalent relationship with the French language, it focuses on the portrayal of affinity between hypotext and hypertext. The study emphasizes a similar concept of the character identical with the narrator “imposing“ a novel’s construction, a similar vision of being in the world and especially a similar need to come up with an original linguistic expression of the topic, which hides the issues of language and narration beneath the surface.